The gut-brain-axis one year after treatment with cladribine tablets in patients with relapsing remitting multiple sclerosis: a pilot study - van Pamelen, Jeske; Rodriguez-Mogeda, Carla; van Olst, Lynn; van der Pol, Susanne M. A.; Boon, Maarten L.; de Beukelaar, Janet; Gerlach, Oliver H. H.; Budding, Andries E.; Killestein, Joep; de Vries, Helga E.; Visser, Leo H. (Frontiers in Immunology, 2025)
IntroductionCladribine tablets are an effective treatment for relapsing remitting multiple sclerosis (RRMS). However, almost half of the treated patients are not free of disease activity after two years. The aim of this study was to describe the changes that cladribine tablets effectuate in the gut and oral microbiota and the peripheral immunological profile between responders and non-responders.MethodsIn this pilot study of the multicenter, prospective, observational BIA (Brain-Immune-Intestine Axis) study, we included patients aged 18 to 55 years with RRMS who were scheduled to start treatment with cladribine tablets. We assessed the clinical status and the immunological and microbiological profile prior to the start of the treatment and after three and twelve months. At twelve months, we assessed the response status, based on clinical relapses, radiological activity and disability progression on the Expanded Disability Status Scale.ResultsThe first twenty-five patients of the BIA study were included in this analysis. Ten patients (40%) were responders twelve months after treatment. Three months after treatment we found a significant decline of naïve and transitional B cells and memory B cells, and of CD57+ CD56dim NK cells. After twelve months the values recovered to baseline levels, except for the memory B cells. We did not find significant changes of the microbiological profile over time, except for a decline of the phylum Bacteroidetes in the oral samples twelve months after treatment. Baseline values and changes over time did not significantly differ between responders and non-responders. However, several phyla, genera or species (Bacteroidetes, Prevotella, Faecalibacterium prausnitzii) showed a higher relative abundance, and several phyla, genera or species (Proteobacteria, Escherichia coli) had a lower relative abundance in responders compared to non-responders.DiscussionAfter treatment with cladribine tablets, we found significant changes in the immunological landscape. Also, the microbiological profile showed several differences in microbes with known anti- or pro-inflammatory properties between responders and non-responders. Overall, we showed that we can measure a treatment effect from cladribine tablets with our analyses. Future research on data from the BIA study, with a larger sample size and extended follow-up, can possibly confirm the reliability of our findings.